Strategic clarity and its impact on enhancing tax administration practices: applied research in the General Tax Authority (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:                The research aims to demonstrate the impact of strategic clarity in its dimensions represented by clarity (vision, goals, use of resources, procedures, organizational structure, role of employees) and tax management practices represented by (expanding the tax base, using legal authority, employee efficiency, imposing penalties). fines, methods of auditing revenues, applying governance principles). The descriptive analytical approach was adopted, and in light of it, the questionnaire was prepared as a tool for obtaining data from the research sample, which numbered (112) people who were in job positions (general manager, general manager,And a department manager, a first undersecretary, a second undersecretary, and a division official) at the General Tax Authority, where the data was analyzed based on the statistical program (25.SPSS.V) in calculating (weighted arithmetic mean, standard deviation, coefficient of variation, simple and multiple linear regression), The research reached a set of results, the most important of which was the presence of a significant effect of strategic clarity in enhancing tax management practices.